PENGARUH MINAT BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPS SISWA TAMAN DEWASA (SMP) TAMAN SISWA PEMATANGSIANTAR T.A 2024/2025 - Frans Daniel Nababan; Anggun Tiur Ida Sinaga; Herlina Hotmadinar Sianipar (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to obtain knowledge regarding the influence of learning interest and learning motivation on IPS learning outcomes of adult students (SMP) Taman Siswa Academic Year 2024/2025.This research is a quantitative research with Microsoft Excel as the testing medium. The population in this research is 235 people, and the sample used is 148 people. The sampling technique used is Random Sampling. The data collection technique used is a questionnaire (survey). The hypothesis data collection technique uses multiple regression analysis and the coefficient of determination (R2).The research results show that: 1) there is a positive influence of learning interest on IPS learning outcomes of students, this result can be seen in the t-test where the calculated t-value of learning interest (6.854) > t-table value (1.655). 2) there is a positive and significant influence of learning motivation on IPS learning outcomes of students, this result can be seen in the calculated t-value of learning motivation (4.977) > t-table value (1.655), meaning that the variable is significant. 3) learning interest and learning motivation together influence student learning outcomes, this result can be seen in the F-test where the calculated F-value (7.1421) > F-table value (3.0584). The R Square coefficient of determination test is known to be 13.003, which means that 13% of the learning interest and learning motivation variables influence the IPS learning outcomes of adult students (SMP) Taman Siswa Academic Year 2024/2025, and 87% is the influence of other variables that are not examined in this research.